Electrical Characteristics Of PMOS Bulk Mosfet And PMOS Silicon-On-Insulator (SOI) MOSFET Device - Muhammad Nazirul Ifwat, Abd Aziz; Fauziyah, Salehuddin; Anis Suhaila, Mohd Zain; Khairil Ezwan, Kaharudin (Asian Research Publishing Network (ARPN), 2016)
Nowadays, conventional Metal Oxide Semiconductor Field Effect Transistor (MOSFET) has been undergoing major improvement. This improvement is about the introduction of technique that buries the Buried Oxide layer in an MOSFET. This method is known as Silicon-on-insulator (SOI) and it is believed to be able to suppress the Short channel effect (SCE). The SCE is a trigger to diminish the electrical characteristics of a MOSFET device and by introducing this buried oxide layer, it can suppress this SCE. With SCE suppressed by buried oxide layer, electrical characteristics of an MOSFET can be improved; thus the performance of the device can increase tremendously. In this paper, Silvaco ATLAS and Silvaco ATHENA modules have been used. ATHENA module is used to design the structure layout of SOI MOSFET device. Meanwhile, ATLAS module is employed to extract electrical characteristics of design structure of the device. Conventional PMOS Bulk MOSFET and SOI PMOS was designed and constructed. These two electrical results have been observed and analyzed. As a conclusion, the SOI PMOS device is clearly superior compared to the bulk PMOS device.